Free throw shot in basketball: kinematic analysis of scored and missed shots during the learning process - Ammar, A.; Chtourou, H.; Abdelkarim, O.; Parish, A.; Hoekelmann, A. (Sport Sciences for Health, 2016)
The aims of the present study were to analyze selected kinematical parameters of free throw shooting in basketball performed during the learning process and identify which one has a greater effect on success. Fifteen FT attempts performed by 10 male college sports students were recorded with a high-speed camera (200 Hz) and analyzed using the system software SIMI-Motion. Statistical analysis showed that the knee angle helped determine success in FT shooting. Comparing various body angles effect on missed to scored baskets, only knee angles showed a significant difference with a higher value in scored baskets (p < 0.05); more specifically only knee angle was highly correlated to the performance and to the hand velocity with p < 0.05 (r = 0.7and -0.75, respectively). In conclusion, the results of the present study suggest that in an inexpert player, the knee angle is the variable in which a teacher or a coach should intervene to improve the learning outcomes (i.e., performance). However, more studies in this field using expert players are necessary to confirm these suggestions in high-level athletes. ABSTRACT FROM AUTHOR